2021
DOI: 10.3390/agriculture11060494
|View full text |Cite
|
Sign up to set email alerts
|

Planting Systems for Modern Olive Growing: Strengths and Weaknesses

Abstract: The objective of fully mechanizing olive harvesting has been pursued since the 1970s to cope with labor shortages and increasing production costs. Only in the last twenty years, after adopting super-intensive planting systems and developing appropriate straddle machines, a solution seems to have been found. The spread of super-intensive plantings, however, raises serious environmental and social concerns, mainly because of the small number of cultivars that are currently used (basically 2), compared to over 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 103 publications
0
21
0
Order By: Relevance
“…obs.). Therefore, an attempt was made to find traditional olive groves with clear features of cultivation practices of the past, obtaining a glimpse into the state of olive groves in the Mediterranean basin, as well as of Lesvos terraced groves, of previous decades [92]. These practices involved forming the trees' shape to a great height and crown area, in order to overcome environmental stress and to produce larger biennial crops, by being able to accumulate water and nutrients in their large trunk and branches, and their extensive canopy and root system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…obs.). Therefore, an attempt was made to find traditional olive groves with clear features of cultivation practices of the past, obtaining a glimpse into the state of olive groves in the Mediterranean basin, as well as of Lesvos terraced groves, of previous decades [92]. These practices involved forming the trees' shape to a great height and crown area, in order to overcome environmental stress and to produce larger biennial crops, by being able to accumulate water and nutrients in their large trunk and branches, and their extensive canopy and root system.…”
Section: Discussionmentioning
confidence: 99%
“…These practices involved forming the trees' shape to a great height and crown area, in order to overcome environmental stress and to produce larger biennial crops, by being able to accumulate water and nutrients in their large trunk and branches, and their extensive canopy and root system. Modern cultivation practices are substantially differentiated in terms of techniques (irrigation, fertilization, mechanical harvesting, pruning) [92] and shape of trees, aiming at low-growing irrigated trees, with a specific leaf area that produces a constant crop annually [30].…”
Section: Discussionmentioning
confidence: 99%
“…The olive farming sector has to face a growing competition on the international olive oil market [31]. Nowadays the Italian sector is mainly represented by traditional olive orchards (80%), with less than 200 trees/ha, where production costs are higher than revenues, due to low productivity and low level of mechanization for pruning and harvesting operations [32,33]. Moreover, in Apulia, a disease denoted "Olive Quick Decline Syndrome" (OQDS) destroyed, in the last ten years, about 40% of the regional olive orchards.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
“…Affected areas have been reported in other European Countries: Corsica (2015), France (2015), Balearic Islands (2016), Spain (2017), Portugal (2019) [36]. The regeneration strategies concern the replanting of X. fastidiosa-resistant olive tree cultivars [37,38], through the adoption of intensive and superintensive olive-growing models, since they increase yield and reduce the operating costs [33] with an enhancement of level of income. In alternative, a substitution of olive orchard with other crops, similar in soil, climate and technical requirements, have been taken in consideration in developing plans [39] Globally, almond (Prunus dulcis) cultivation is experiencing a period of renewed interest mainly due to a strong interest in the health properties of the fruits.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
“…During December end and January, olive trees can be pruned. Lo Bianco et al (2021) found that heavy pruning of olive cultivar Frantoio made it more likely to produce fruit. Pruning thorough use of chemicals i-e. Hexaconazole treatment is also a way to increase fruit set in a way that is both safe and effective.…”
Section: Pruningmentioning
confidence: 99%